Fiqh Ramah Lingkungan (Fiqh Bi'ah): Konsep Pengembangan Berkelanjutan Produk Ramah Lingkungan: Environmentally Friendly Fiqh (Fiqh Bi'ah): The Concept of Sustainable Development of Environmentally Friendly Products - Alvan Fathony; Syafiqotunnafila (QULUBANA: Jurnal Manajemen Dakwah, 2024)
In economic development, the concept of a green economy supports human well-being and pays attention to the preservation of the environment and ecosystems. However, from a negative perspective, economic development can also lead to the loss of natural resources due to excessive management, pollution of land, water, and air by industrial pollution, floods, and the impacts of climate change. The ideal concept of sustainable development can be found in Islam. At least there are basic rules that support sustainable development, namely the application of fiqh al-bi'ah based on maqashid sharia to manage Islamic resources in the economy. This type of research is a descriptive research paper with a qualitative approach. The research procedure produces descriptive data in the form of written words from people and observed behaviors. The results of this research indicate that the application of Islamic fiqh al-bi'ah can significantly contribute to global efforts to address environmental challenges and achieve fair and inclusive sustainable development.